2018
DOI: 10.1016/j.cardfail.2017.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Cannula and Pump Positions Are Associated With Left Ventricular Unloading and Clinical Outcome in Patients With HeartWare Left Ventricular Assist Device

Abstract: Background Cannula and pump positions are associated with clinical outcomes such as device thrombosis in patients with HeartMate II; however, clinical implications of HVAD (HeartWare International, Framingham, Massachusetts) cannula position are unknown. This study aims to assess the relationship among cannula position, left ventricular (LV) unloading, and patient prognosis. Methods and results Twenty-seven HVAD patients (60.0 ± 12.6 years of age and 19 males [70%]) underwent ramp test. Device position was q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 19 publications
2
42
1
Order By: Relevance
“…Malpositioned LVAD inflow cannula is associated with pump failure, thrombosis, suction events, and VT (3,4). VT is associated with decreased pump flow, right ventricular failure, and increased overall morbidity and mortality in LVAD-supported patients (4).…”
Section: Mobile Inflow Cannula Leading To Positional Ventricular Tachmentioning
confidence: 99%
“…Malpositioned LVAD inflow cannula is associated with pump failure, thrombosis, suction events, and VT (3,4). VT is associated with decreased pump flow, right ventricular failure, and increased overall morbidity and mortality in LVAD-supported patients (4).…”
Section: Mobile Inflow Cannula Leading To Positional Ventricular Tachmentioning
confidence: 99%
“…4 Similarly, the inability to reduce the PAWP with LVAS speed increase is also associated with worse outcomes. 3 The correlation between PAWP Δramp and TMP LV suggests that biventricular interaction may play a role: patients with elevated PAWP and low CVP (high TMP LV ) have a higher PAWP var and PAWP Δramp , and conversely those with elevated PAWP and high CVP (low TMP LV ) have lower PAWP var and PAWP Δramp . One may hypothesize that the presence of a low TMP LV indicates the presence of a 'pseudoconstrictive' state due to increased cardiac volumes and/or right ventricular failure.…”
Section: Figurementioning
confidence: 99%
“…In one cohort of 35 LVAS patients, only 43% had normal central venous pressure (CVP) and/or pulmonary artery wedge pressure (PAWP) at the time of haemodynamic assessment with right heart catheterization (RHC), with 57% achieving normal filling pressures at the end of ramp speed adjustment . Further studies have suggested that inability to normalize filling pressures during speed adjustment confers a worse prognosis . Even in the hands of LVAS‐trained clinicians with the aid of real‐time invasive haemodynamic data, over 40% of patients remain non‐optimized after LVAS speed adjustment.…”
mentioning
confidence: 99%
See 2 more Smart Citations